Exploration of the role of immune cells and cell therapy in hepatocellular carcinoma - Tao Zhang; Cong Ren; Zhanyu Yang; Ning Zhang; Haowen Tang (Frontiers in Immunology)
Hepatocellular carcinoma stands as one of the foremost contributors to cancer-associated fatalities globally, and the limitations of traditional treatment methods have prompted researchers to explore new therapeutic options. Recently, cell therapy has emerged as a promising approach for HCC, showing significant potential in improving patient outcomes. This review article explores the use of cell therapy for HCC, covering different types, the mechanisms behind their effectiveness, recent advancements in clinical trials, and ongoing challenges. This article aims to provide insightful perspectives for future research and clinical applications in treating HCC by synthesizing current knowledge.